Método colorimétrico para determinação de dióxido de nitrogênio atmosférico com preconcentração em coluna de c-18 - Ugucione, Cássia [UNESP]; Gomes Neto, José de Anchieta [UNESP]; Cardoso, Arnaldo Alves [UNESP] (Sociedade Brasileira de Química, 2002)
An alternative analytical method for nitrogen dioxide (NO2) in atmosphere was developed. The collection of NO2 is performed by a Sep-Pack C-18 cartridge impregnated with 11% (v/v) of triethanolamine plus 3,6 % (v/v) of ethylene glycol plus 25 % (v/v) of acetone combined solution. When the impregnating is used, NO2 is collected with good repeatibility (CV = 3,3 %). The NO2 absorbed in the sampler was stripped from the sorbent with a methanol 5% (v/v) aqueous solution and was determined by colorimetry as nitrite by using the Griess-Saltzman reagent. The detection limit of 1,4 ppb for 60 min sampling at 0,5 L min-1 flow rate was obtained. Preparation and conditioning procedures for TEA-C-18 cartridge, sampling flow rate, absorption capacity and interference of other species are discussed.
Colorimetric determination of atmospheric nitrogen dioxide using preconcentration on c-18 cartridge
Keywords: nitrogen dioxide; triethanolamine; Griess Saltzman reagent